Service quality and customer preference towards Islamic banking in Malaysia: A study using Carter model - Lamsali, Hendrik; Che Razak, Razli; Mad Lazim, Halim; Ismail, Hirun Azaman; Ahmad Arshad, Darwina; Adnan, Khairul Anuar (2005)
This study has been carried out to identify elements of service quality influencing customers’ preference towards Islamic Banking products and services in Malaysia. An alternative service quality measurement model called CARTER developed by Othman and Owen (2001) has been used particularly to address elements of compliance to Shari’ah in addition to Parasuraman’s service quality measurement of five original dimensions. Data collection covering 5 largest cities from 5 states and four regions of peninsular Malaysia has been successfully conducted in which 1036 questionnaires have been returned. Respondents were randomly chosen from two of the largest banks in Malaysia in which one is Islamic bank and the latter is conventional bank offering Islamic banking scheme products and services. Multiple Regression analysis has been used to determine critical elements of service quality in which respondents perceived more in influencing them to choose Islamic banking products and services.